2010
DOI: 10.1063/1.3498809
|View full text |Cite
|
Sign up to set email alerts
|

Reset dynamics and latching in niobium superconducting nanowire single-photon detectors

Abstract: We study the reset dynamics of niobium ��Nb�� superconducting nanowire single-photon detectors ��SNSPDs�� using experimental measurements and numerical simulations. The numerical simulations of the detection dynamics agree well with experimental measurements, using independently determined parameters in the simulations. We find that if the photon-induced hotspot cools too slowly, the device will latch into a dc resistive state. To avoid latching, the time for the hotspot to cool must be short compared to the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 33 publications
0
84
0
Order By: Relevance
“…Phonons and quasiparticles diffuse from the hotspot to the surrounding superconductor where they interact with the superconducting bath, depleting the local Cooper pair population as they relax back to equilibrium 9 . In the case of thin-film NbN, out-diffusion of hot electrons is the primary means of thermal energy transfer from the hotspot to the surrounding material 10,11 ; the characteristic diffusion coefficient for non-equilibrium electrons has been measured 12 to be 45 nm 2 /ps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phonons and quasiparticles diffuse from the hotspot to the surrounding superconductor where they interact with the superconducting bath, depleting the local Cooper pair population as they relax back to equilibrium 9 . In the case of thin-film NbN, out-diffusion of hot electrons is the primary means of thermal energy transfer from the hotspot to the surrounding material 10,11 ; the characteristic diffusion coefficient for non-equilibrium electrons has been measured 12 to be 45 nm 2 /ps.…”
mentioning
confidence: 99%
“…The simulation used no free parameters-we instead employed measurements from the device as well as empirical parameters for thin-film NbN found in the literature 11,12 . The simulation results showed that when a hotspot was formed in the choke of the nTron, the effective electron temperature T e of the surrounding ~100 nm was increased.…”
mentioning
confidence: 99%
“…Thus it is desirable to make R R as large as possible without causing the SNSPDs to latch into the normal state due to speedup of the current recovery into the pixel. 14,15 For the 4-pixel array presented here, we found that 25 Ω was large enough to accurately discriminate the row pulse without causing the SNSPDs to latch. For the series resistor R S there is no gain in performance when the value of R S is increased.…”
mentioning
confidence: 90%
“…The external detection electronics would then be similar to that proposed by Divochiy et al [13]. To determine the detection area we provide an example of relatively standard dimensions for NbN nanowire detectors [9,10,12,14,15,16]. The device shown in figure (2) has six pixels in each arm and 6 arms.…”
Section: A Three Layer Architecturementioning
confidence: 99%